Implementasi Platform Tepat Daya Bank BTPN Syariah dalam Mendukung Pengembangan dan Peningkatan Skill Usaha Mikro Desa - Daniswara, Edo; Oktafia, Renny; Laily, Fauzatul (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research was conducted with the aim of knowing the implementation of the Prestasi Daya Platform Application which was introduced to Bank BTPN Syariah customers through the University Friendship Program by BTPN Syariah in supporting Bank BTPN Syariah customers, especially those who have MSME businesses in increasing customer knowledge regarding tips on entrepreneurship in the sub-district area. Pujon, Malang Regency. The research in this journal article uses the case study qualitative method because of the closeness and ease of finding accessible information related to the research being conducted and the limited time and place to conduct the research. Bank BTPN Syariah specifically created an application called the Exact Daya Platform as well as running an Internship program with the theme Friends of University Daya which aims to improve the quality of MSMEs from its customers by assigning apprentice students through gradual mentoring providing direct education to its customers regarding tips in developing its business and also supported by the introduction of the Prestasi Daya Platform Application which can be used as a means of self-learning for its customers in the future after the mentoring period is over. With the Precise Daya Platform application, it is hoped that BTPN Syariah bank customers can develop their business independently and better in the future. Keywords: BTPN Syariah, Small and Medium Enterprise (SME), Business Development, Business Assistance